The Impact of Generative AI On Political Participation and Information Vulnerability of Generation Z: A Literature Review - Muhammad Yazid Khofi (JURNAL ILMIAH DETUBUYA, 2025)
This study comprehensively analyzes the impact of generative AI on the political participation and information vulnerability of Generation Z, employing library research and literature review approaches. Data were collected from books and scientific articles sourced from Google Scholar, Scopus, DOAJ, and Scispace, with publications spanning the years 2018–2025. The selection process was conducted in stages, involving the screening of titles, abstracts, and full texts based on inclusion criteria that emphasized the relevance of topics related to generative AI, digital politics, and Generation Z. Thematic analysis was employed to synthesize the findings across studies. The results of the study indicate that generative AI is no longer simply a communication tool, but rather a strategic actor shaping the production and distribution of political information through algorithmic personalization, accelerated narrative circulation, and amplified emotional communication. Its impact is ambivalent; AI can increase political participation, but also trigger misinformation, manipulation, and erosion of public trust. Gen Z's information vulnerability is understood as the result of the interaction between platform design, algorithms, and the information ecosystem, not simply an individual limitation. This study recommends strengthening AI literacy, transparent regulation, and political data governance to maintain the quality of digital democracy.